Exploring Professional Communication : Language in Action. - Schnurr, Stephanie (Routledge introductions to applied linguistics., 2012)
Routledge Introductions to Applied Linguistics is a series of introductory level textbooks covering the core topics in Applied Linguistics, primarily designed for those beginning postgraduate studies, or taking an introductory MA course as well as advanced undergraduates. Titles in the series are also ideal for language professionals returning to academic study. The books take an innovative 'practice-to-theory' approach, with a 'back-to-front' structure. This leads the reader from real-world problems and issues, through a discussion of intervention and how to.